Operative correction of judoists’ training loads on the base of on-line monitoring of heart beats rate - Yong Qiang Liu (Physical Education of Students, 2015)
Purpose: ensure increase of effectiveness of training process’s control by means of operative correction of training loads of different qualification judo wrestlers’ heart beats rate indicators. Material: the research was conducted on the base of Brest SCJSOR № 1. Judo wrestlers of different sport qualification (age 17-19 years old, n=15) participated in the research. Monitoring of judo wrestlers’ heart beats rate was carried out with the help of system “Polar”. Results: we have found factorial structure of functional fitness in every profile of sportsmen. Model characteristics of judo wrestlers were supplemented with the most important sides of functional fitness. Analysis of indicators of restoration effectiveness indicators (REI) in both groups of judo wrestlers showed high level of organism’s responsiveness to training load of special and power orientation in comparison with speed power load. We have worked out algorithm of operative correction of training loads by indicators of heart beats rate in training process, depending on orientation and intensity of loads’ physiological influence on judo wrestler. Conclusions: Telemetric on-line monitoring of sportsman’s heart beats rate and calculation of REI permit to objectively assess effectiveness of training’s construction and of micro-cycle in total and detect in due time the trend to development of over-loading and failure of adaptation.